2014
DOI: 10.1177/1535370214553898
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of multipotent mesenchymal stem cells in nasal polyps

Abstract: Mesenchymal stem cells (MSCs) are multipotent progenitor cells in adult tissues. This study aimed to investigate nasal polyp (NP) tissues as a potential new source of multipotent MSCs that maintain their stemness and differentiation potential following multiple rounds of passaging. NP tissues were obtained from 10 patients during endoscopic sinus surgery. After isolating and culturing NPderived MSCs (npMSCs), the expression levels of the surface markers CD34, CD44, CD45, CD73, CD90, CD105, CD106, CD146 and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Until now, only a few researchers have addressed this issue. Cho et al (2015) isolated and characterized MSC in nasal polyps and proposed nasal polyp-derived MSCs as an alternative source of MSCs. Otherwise, Pezato et al (2014) demonstrated that bone marrow-derived MSCs had an immunoregulatory effect on immune cells (especially T cells) derived from nasal tissue affected by CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only a few researchers have addressed this issue. Cho et al (2015) isolated and characterized MSC in nasal polyps and proposed nasal polyp-derived MSCs as an alternative source of MSCs. Otherwise, Pezato et al (2014) demonstrated that bone marrow-derived MSCs had an immunoregulatory effect on immune cells (especially T cells) derived from nasal tissue affected by CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, researchers linked the pathogenesis of nasal polyps to the presence and differentiation of mesenchymal stem cells (MSC) (Cho et al 2014(Cho et al , 2015Pezato et al 2014), pathological changes in the epithelium (de Borja Callejas et al 2014;Li et al 2014;Wiszniewski et al 2006;Yu et al 2014) or to single stem cell markers like stem cell factor, Nestin, and BMI-1 (Kim et al 1997(Kim et al , 2009Kowalski et al 2005). The overall stemness and for example neuronal differentiation potential of nasal polyps are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometric analyses were employed to mesenchymal stem cell characterization by CD73, CD90, and CD105 positive cell surface marker expression, while being negative for CD34, CD45, and HLA-DR surface markers [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs were washed with phosphate buffered solution (pH 7.4) and incubated in the dark for 1 h at room temperature with CD45-FITC or CD34-PE-Cy7 antibodies (BD Pharmingen, San Diego, CA, USA), following the protocol previously described [12]. The specific fluorescence of 10,000 cells was analyzed on FACScalibur (Becton Dickinson, Franklin Lakes, NJ, USA) using Cell Quest Pro software.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…They are characterized by a high rate of renewal, proliferative ability and multipotentiality. The latter term refers to their ability to differentiate into various cell lineages, such as chondrocytes [Mathieu et al, 2014], osteocytes [Cho et al, 2014], adipocytes [Casado et al, 2012], neurons [Nandy et al, 2014], and myocytes [Meligy et al, 2012].…”
Section: Introductionmentioning
confidence: 99%